Split Ends: Sometimes the End is Really the Beginning - Billerbeck, Kristin (Thomas Nelson, Inc., 2007)
She's armed$1 (Bwith hot irons, sharp shears, and a flair for color. She's dangerous$1 (Btruly bad news for bad hair. And she's going to do whatever it takes to make a place for herself in the exclusive Beverly Hills salon. Even if that means sweeping hair, emptying trash, scrubbing dummy heads, and making soy lattes for the stars that come to Yoshi's salon. Even if it means hiding the fact that she's not really an up-and-comer from New York, but a drunk's daughter from small-town Wyoming. Even if it means igoring her attraction to a tall, dark stranger in a fedora who just stepped off the elevator . . . and into her heart. But can a talented hairdresser from the sticks really make it in image-obsessed L.A.? And can she ever find true love and real success in a town that wrote the book on fake?s
Keywords: Fiction; Fiction / Hairdressing